Effect of desert particulate composition on helicopter engine degradration rate - Bojdo, M.; Filippone, A. (My University, 2014)
Abrasive, short-term damage to helicopter engines by quartz particles can be mitigated by the use of an inlet particle separator. However, such devices fail to remove the finest particles that have significantly different mineralogy to quartz. If these particles reach the hot end components, they may form deposits on the vane surfaces, or clog cooling holes. In the former case, a choking effect is created leading to a reduction in the surge margin; in the latter, an increase in heat transfer to the blade thence reduction in life may result. Prediction of this is limited by the myriad of contributory factors: the likelihood of a particle adhering to a surface depends on its phase and viscosity which changes along its path; the rate of change of state depends on the physical and chemical properties of the particle, which vary according to global location and inlet separator effectiveness. This contribution summarises the process of turbine degradation in desert-based helicopters, and proposes a novel approach to its prediction